The Janus-Faced Attitude of Global International Law to Democracy - Mikołajczyk, Barbara (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
This paper considers the relationships between global international law and democracy as well as between democracy and human rights. Its primary assumption is that some obstacles to democracy are rooted in international law itself. Simultaneously, international law, particularly international human rights law, is also undeniably the flywheel pushing countries towards democratic governance, of which the protection of human rights is an essential element. Therefore, this paper examines the attitude of global international law to democracy and the interplay between democracy and human rights. It also traces whether a human right to democracy arises from international law. This research shows that international law has two faces. The first shows that international law is not conducive to, or at least is indifferent to, democracy. At the same time, there is another face of international law revealed by international human rights law as some pillars of democracy and the rule of law, are protected by human rights treaties. The universal hard and soft international laws and output of human rights bodies show that democracy should go hand in hand with the rule of law and human rights.